Tumor microbial diversity and compositional differences among women in Botswana with high‐grade cervical dysplasia and cervical cancer. Issue 8 (August 2020) - Sims, Travis T; Biegert, Greyson W G; Ramogola‐Masire, Doreen; Ngoni, Kebatshabile; Solley, Travis; Ning, Matthew S; El Alam, Molly B; Mezzari, Melissa; Petrosino, Joseph; Zetola, Nicola M; Schmeler, Kathleen M; Colbert, Lauren E; et al.
ABSTRACT : Introduction : We characterized the cervical 16S rDNA microbiome of patients in Botswana with high‐grade cervical dysplasia and locally advanced cervical cancer. Methods : This prospective study included 31 patients: 21 with dysplasia and 10 with cancer. The Shannon diversity index was used to evaluate alpha (intra‐sample) diversity, while the UniFrac (weighted and unweighted) and Bray‐Curtis distances were employed to evaluate beta (inter‐sample) diversity. The relative abundance of microbial taxa was compared among samples using linear discriminant analysis effect size. Results : Alpha diversity was significantly higher in patients with cervical cancer than in patients with cervical dysplasia (P<0.05). Beta diversity also differed significantly (weighted UniFrac Bray‐Curtis, P<0.01). Neither alpha diversity (P=0.8) nor beta diversity (P=0.19) varied by HIV status. The results of linear discriminant analysis effect size demonstrated that multiple taxa differed significantly between patients with cervical dysplasia vs cancer. Lachnospira bacteria (in the Clostridia class) were particularly enriched among cervical dysplasia patients, while Proteobacteria (members of the Firmicutes phyla and the Comamonadaceae family) were enriched in patients with cervical cancer. Discussion : The results of our study suggest that differences exist in the diversity and composition of the cervical microbiota between patients with cervical dysplasia and patients with cervical cancer in Botswana. Additional studies are warranted to validate these findings and elucidate their clinical significance among women living in sub‐Saharan Africa, as well as other regions of the world.